Mucosal-Associated Invariant T Cells in Chronic Inflammatory Liver Disease - Bolte, Fabian J.; Rehermann, Barbara (Seminars in Liver Disease, 2018)
The broadening field of microbiome research has led to a substantial reappraisal of the gut–liver axis and its role in chronic liver disease. The liver is a central immunologic organ that is continuously exposed to food and microbial-derived antigens from the gastrointestinal tract. Mucosal-associated invariant T (MAIT) cells are enriched in the human liver and can be activated by inflammatory cytokines and microbial antigens. In chronic inflammatory liver disease, MAIT cells are depleted suggesting an impaired MAIT cell-dependent protection against bacterial infections.
Keywords: mucosal-associated invariant T cells; hepatitis; inflammation; cirrhosis; liver metastases; gut–liver axis.